2018
DOI: 10.1111/asj.12967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an immune stimulant, inactivated Mycobacterium phlei, on the growth performance as well as meat quality of fattening pigs

Abstract: Inactivated mycobacterium phlei (M. phlei) is well known for its immune-stimulatory functions in humans and livestock, but less information is available about the influence on meat quality of pigs when used as a feed additive. This study was designed to evaluate the effects of inactivated M. phlei on growth performance as well as meat quality of fattening pigs. A total of 240 cross-bred pigs ([Landrace × Yorkshire] × Duroc) with initial body weight of 80.14 ± 0.29 kg were randomly allocated to five treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Fatty acid analysis of the Longissimus dorsi showed a slight decrease in saturated and an increase in monounsaturated and polyunsaturated fatty acids. At the same time, an improvement in the quality of meat was observed with an increase in the content of intramuscular fat due to the inactivation of some genes [96].…”
Section: Regulation Of Pork Composition Using Nutritional Factorsmentioning
confidence: 88%
See 2 more Smart Citations
“…Fatty acid analysis of the Longissimus dorsi showed a slight decrease in saturated and an increase in monounsaturated and polyunsaturated fatty acids. At the same time, an improvement in the quality of meat was observed with an increase in the content of intramuscular fat due to the inactivation of some genes [96].…”
Section: Regulation Of Pork Composition Using Nutritional Factorsmentioning
confidence: 88%
“…Several other authors have studied ways to improve the quality and oxidative stability of pork using nutritional factors [92][93][94][95][96][97].…”
Section: Regulation Of Pork Composition Using Nutritional Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that M. phlei regulates animal growth. Zhong et al (2018) added different levels of inactivated M. phlei preparations to the diets of fattening pigs and determined the average daily feed intake and average daily weight gain of pigs after 30 days. These authors also determined the intramuscular fat content, pH, drip loss, cooking loss and filter paper fluid uptake of Longissimus dorsi in pigs and found that feeding the inactivated M. phlei preparations decreased the contents of some saturated fatty acids in fattening pigs.…”
Section: Growth Performance Regulationmentioning
confidence: 99%